TEACHER DIFFICULTIES IN USING AUDIO VISUAL MEDIA IN LEARNING ACTIVITIES AT AISYIYAH KINDERGARTEN BUSTANUL ATHFAL 17 MEDAN - Fildzah Azrina; Adinda Fristi; Suniyya Razani; Hani Almaida Yanni; Irfan Sawaluddin; Alya Arsanti (Proceeding International Seminar of Islamic Studies, 2022)
This research is intended to find out what difficulties are faced by kindergarten teachers in using Audio Visual Media. The approach used in this study is a qualitative approach, while the type of research used is descriptive research. Data collection techniques were carried out using observation, and interviews with class teachers. The place and time of the research was carried out at Aisyiyah Kindergarten Bustanul Athfal 17 on August 1, 2022. The results showed that teachers faced difficulties in terms of time to make materials and also prepare tools to support the use of audio-visual media. And to overcome these difficulties, teachers collaborated to help each other to understand more deeply about the use of audio-visual media. With audio-visual media, children will give a very good / positive response and also using audio-visual media can help teachers when carrying out the teaching and learning process in class without having to explain at length. Children are also more enthusiastic and motivated in the learning process.